First report of pulmonary disease associated with Nicoletella semolina in a horse in New Zealand. Issue 1 (2nd January 2021) - Riley, CB; Aldrich, ED; Pemberton, SL; Mirza, AA
ABSTRACT: Case history: A 9-year-old warmblood gelding with a history of chronic intermittent tachypnoea and dyspnoea was presented for evaluation and removal of a mass on the left side of the neck. A fibrous mass adherent to the left jugular vein developed and was removed surgically 6 weeks later, at which time the owner requested an evaluation of the cause of the persistent respiratory signs first noted on primary admission. Clinical findings and treatment: Clinical findings included coarse lung sounds on thoracic auscultation, tracheal wheeze, and an abnormal trans-tracheal aspirate. These findings, in addition to the results of ultrasonographic imaging of the thorax and transtracheal cytology, were suggestive of bacterial bronchopneumonia. Initial antimicrobial therapy included I/M 22 mg/kg procaine penicillin every 12 hours and I/V 6.6 mg/kg gentamicin sulphate every 24 hours. The horse's clinical signs improved within 36 hours. It was discharged after 6 days, and at the owner's request antimicrobial therapy was changed to 25 mg/kg trimethoprim/sulphadimidine to be given orally every 12 hours for 10 days. One month later, the horse had recovered and there were no further complications reported by the owner except for an occasional cough while grazing Laboratory findings: Bacterial culture of transtracheal wash fluid resulted in the isolation of Nicoletella semolina as the sole organism, later confirmed by genotyping. Attempts to subculture the organism for antimicrobial susceptibility testing were unsuccessful. Diagnosis: Infectious bronchopneumonia associated with Nicoletella semolina Clinical relevance: Further work is required to determine whether N. semolina is acting as an opportunistic commensal of the equine respiratory tract or a primary pathogen. However, this article reports the first instance in New Zealand of an association between the presence of this organism and respiratory disease in a horse.